Middle school general music : the best part of your day - McAnally, Elizabeth Ann.; MENC, the National Association for Music Education (U.S.) (Lanham, Md. : Rowman & Littlefield Education, 2009)
"Create a viable, participatory program that will motivate your students and have them singing with enthusiasm with Middle School General Music: The Best Part of Your Day. A welcome guidebook for music teachers trying to navigate the sometimes turbulent waters of middle school general music, it offers strategies and lessons that have been tested and refined in the music classroom." "Following the nine National Standards for Music Education, each chapter is full of tips and lessons to help middle schoolers meet high standards in their understanding of music. From a music critics unit to composition projects and rhythm games, you'll find plenty of tips for working with young adolescents. A chapter full of suggested resources steers you to materials appropriate for middle-level students. Bolster your program with the discussion on why general music is so vital in middle school. If your music classes feel like the perfect storm, let Elizabeth McAnally make them the best part of your day."--BOOK JACKET.
"Published in partnership with MENC: The National Association for Music Education."
Includes bibliographical references (p. 89).
Keywords: School music -- Instruction and study -- Outlines, syllabi, etc; School music -- Instruction and study -- Handbooks, manuals, etc